Articulating Upgrading: Island Developing States and Canned Tuna Production. (November 2013) - Havice, Elizabeth; Campling, Liam
Recently, researchers have drawn attention to an inclusionary bias in commodity chain research and proposed a 'dis/articulations' project aimed at drawing out how things included in, as well as excluded or expulsed from, production processes mutually, and often simultaneously, constitute commodity chains. The purpose of this paper is to situate the dis/articulations project in debates and policy proposals that identify 'upgrading' within a commodity chain as a pathway to development. We draw on foundational uses of the term 'articulation' in historical materialism to complicate linear notions of 'upgrading as development' before developing a framework for capturing the nonlinear dynamics of upgrading in a particular commodity chain. Our case study explains how small states that interact with the tuna commodity chain rise and fall (individually and in relation to each other), and have remained surprisingly relevant, though often at high cost, in competitive standardized manufacture. We suggest that, with careful attention to method in concept building, researchers can develop the dis/articulations project to create space for systematic assessment of the inclusionary bias in upgrading debates and policy formulations.